Diffusion Monte Carlo simulations of methanol-water clusters - Iosue, J; Benoit, D; Clary, D (1999)
We report the ground-state properties of several partially deuterated CH3OH[H2O]n (n=1, 2) clusters calculated with the rigid-body diffusion Monte Carlo method. The dimer has two distinct isomers with methanol-donor or water-donor structures. The dimer complex was found to prefer a water-donor structure and the calculated rotational constants for this isomer compare favorably with results obtained in recent experiments. The ground-state structure of the CH3OH[H2O]2 trimer was found to be cyclic.